Alain Mabanckou et la pigmentation de l'edition francaise - De La Roche Souvestre, Marie Arielle (French Language and Literature, 2016)
In 2006 for the first time in the history of French literature, five out of the seven most prestigious French literary prizes were attributed to foreign writers. To the signatories of a manifesto published a few months later, this meant that francophone writers no longer belonged to the margins of French literature. Indeed, a restructuring of the literary landscape was in order. They demanded that French and francophone literatures be merged into a single literary field which would be known as the world literature in French and within which authors would not be differentiated according to their nationality. Non-French writers would no longer be edged out into specialized collections, thus only reaching a very narrow and very specific readership. Today, few of the desired changes can be observed. The signatories' continued reliance on major Parisian publishing houses is a clear indication that France remains at the forefront and centre of French-language literature. A close look at the editorial journey of Alain Mabanckou, one of the manifesto's most fervent advocates, corroborates this statement. While he made a gradual progression towards Gallimard's illustrious Collection Blanche, he is still systematically portrayed above all as an African writer through the use of racialised paratextual elements. The deep-rooted hegemony of France cannot be toppled overnight. After situating Alain Mabanckou's position within the literary hierarchy thanks to an analysis of his editorial journey and an overview of his works' paratextual representation, this dissertation delves into the author's usage of fiction as a means of sensitising readers to the struggles of non-French writers. A three-tiered evolution can be observed throughout his career beginning with an unconditional admiration for France in his first novel Bleu-blanc-rouge (1998). He then adopted a more patriotic stance in African Psycho (2003a) by advocating creative authenticity before overtly criticising France's rigid literary and language conventions in Verre Cassé (2005). Interestingly, he also praised the United States' growing role in facilitating the creative process for French-language writers - an interesting lead for future research.